2017 AIChE Spring Meeting & 13th Global Congress on Process Safety : perspectives on process safety from around the globe (Center for Chemical Process Safety/AIChE, 2017)
Perspectives on Process Safety from Around the World is consist of sessions that strive to provide a space for different regions around the world to get together at the Global Congress and discuss the issues that are significantly impacting the development in Process Safety in their regions, considering the particular needs of language, and cultural characteristics of each one.
Keywords: Chemical process control.; Chemical plants -- Safety measures.; elektronické knihy; electronic books